Chemical Analysis, Physical Stability, and Antibacterial Activity of Nanoemulgel Hand Sanitizer Formulated with Citrus aurantifolia Essential Oil and Herbal Emollients - Intan Kurnia Putri; Maya Uzia Beandrade; Reza Anindita (Biology, Medicine, & Natural Product Chemistry, 2025)
One of the most purchased hand sanitizer products by the public since the COVID-19 pandemic is hand sanitizer. However, alcohol-based hand sanitizer products often cause toxic effects and bacterial resistance. Therefore, alternative efforts are needed to replace antibacterial raw materials instead of alcohol, namely lime peel essential oils (Citrus aurantifolia) with Aloe vera and Calendula officinalis emollients.  This study aims to evaluate the physicochemistry, physical stability, and antibacterial affectiveness of the a nanoemulgel handsanitizer formula composed of active lime peel essential oils supplemented with Aloe vera and Calendula officinalis emollients. The design of this research is an experiment. Research treatment: formula (F) hand sanitizer nanoemulgel F1 2%, F2 4%, and F6 6%. Essential oil component test using GC-MS method, SNEEDS physical stability includes centrifugation test, freeze-thawing, transmittance, particle size, polydispersity index (PI), potential zeta, physical stability of nanoemulgel hand sanitizer, including organoleptic, homogeneity, pH, and viscosity test, antibacterial efficacy test using hand swabbing method. The results: GC-MS analysis of the components of lime peel essential oils: alpha-pinene (8.87%), linalool (0.58%), and L-alpha-terpineol (8.98%). All SNEEDS formulas and nanoemulgels were stable during 6 weeks of storage. Formulas F2 4% and F3 6% reduced the percentage (%) of hand bacterial colonies to 74% and 75%. The results of the one-way ANOVA showed a significant decrease (p < 0.05) in the number of bacterial colonies after using nanoemulgel hand sanitizer, especially in the F2 and F3 formulas. The conclusion is that Formula 3 (F3 6%) hand sanitizer is recommended as the best candidate for the development of a nanoemulgel hand sanitizer based on lime essential oil, as it offers the most optimal combination of physical stability, chemical stability, and biological effectiveness.